The More Doctors Program and the changing role of the State in the regulation and organization of medical education - Hêider Aurélio Pinto; Rosemarie Andreazza; Renato Janine Ribeiro; Maria Rosa Loula; Ademar Arthur Chioro dos Reis (Faculdade de Medicina de Botucatu (Unesp), 2019)
ABSTRACT The More Doctors Program has been considered, in recent studies, the most important normative change of the State's attributions in the organization of the education of human resources for the Brazilian National Health System (SUS). This article analyzes the most structuring axis of the program, education in health, by revising literature, and analyzing documents and databases in order to describe its model as a public policy and discuss which normative changes had an effect on the State's action. The article identifies institutional changes in the Brazilian Ministry of Health and Ministry of Education, in the reorientation of medical education, in the expansion and redistribution of undergraduate and residency seats, and in the creation of public policy instruments to plan, regulate and assess the education of specialists. The paper is concluded by identifying interruptions in the program's structuring actions and objectives, and goals and objectives that will probably not be met within the established deadlines.